Análisis de los contratos discográficos más usuales: el de producción fonográfica y el de licencia - Bajarlía, Daniel (2009)
This article will analyze the two contracts most used in the record\nindustry?the phonograph production contract and the license contract. Phonograph\nproduction contracts are an hybrid type between a manufacture contract\nand an edition contract, while license contracts are an imperfect assignment of\nrights, as industrial licenses. Both have special features given the fact that their\nsubject matter is an intellectual property work. The theoretical and legal analysis\nof these contracts will be combined with real anecdotes of the music industry\nshowing the practical application of its provisions and the possible conflict of\nrights that may arise between parties